Including the isolated: Place, rurality, and the state in regional Western Australia during the COVID-19 pandemic and vaccine rollout - Sean McDonell; Katie Attwell; Lara McKenzie (Elsevier, 2024)
The rapid transmission of SARS-CoV-2 demonstrated the world's interconnectedness, yet it also highlighted the importance of distance and place in the spread of virus and the distribution, access, and uptake of vaccinations. We examine how people in rural spaces living in a high income country, Australia, thought about the state's governance of them during the pandemic and vaccine rollout, particularly regarding government's responsibility for them as citizens. Utilising interviews with regionally located Western Australians, we explore people's feelings of isolation, otherness, and subordination to governments perceived as distant and disinterested, as well as their sense of safety and seclusion. Distance-physical and imagined-plays a key role in rural understandings of individual-state relations and impacted responses to lockdowns and vaccine eligibility policies. We demonstrate how feelings of political distance and isolation were exacerbated by the pandemic-leading to resistance to government policies-and show how this informed and reflected rural Western Australians' self-understandings. We find that a sense of separation and subordination oriented people towards specific kinds of vaccine behaviours, including 'constructive deviance', in which people sought vaccinations on their own terms.